ANALISIS AGRESIVITAS PELAPORAN KEUANGAN, AGRESIVITAS PAJAK DAN KEPEMILIKAN KELUARGA - Bambang Bambang; Hanny Savira; Akram Akram (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2017)
The aim of this study is to analyze the effect between of financial reporting aggressiveness, tax aggressiveness and family ownership. The analysis was performed in 39 manufacturing companies which are listed in Bursa Efek Indonesia during the period 2013-2014 by using multiple linear regression analysis. The results of the study show that financial reporting aggressiveness affects tax aggressiveness and tax aggressiveness affects the financial reporting aggressiveness. This proves that the companies earning management affected by aggressive tax and tax management actions are also usually affected by the actions of earning management so that the company's financial position looks good. However, the study found that the family ownership does not affect the financial reporting aggressiveness or tax aggressiveness. This study also uses three control variables, namely profitability, leverage, and the size of the company. The results showed that the size of the company affects financial reporting aggressiveness, while profitability and leverage were found to have no effect on the financial reporting aggressiveness. Furthermore, while the profitability showed influence on the tax aggressiveness, the leverage and the size of the company showed no influence on the tax aggressiveness.